2021
DOI: 10.1002/smll.202102598
|View full text |Cite
|
Sign up to set email alerts
|

A Targeted Nanosystem for Detection of Inflammatory Diseases via Fluorescent/Optoacoustic Imaging and Therapy via Modulating Nrf2/NF‐κB Pathways

Abstract: Inflammatory diseases are sometimes devastating and notoriously difficult to treat. Precisely modulating inflammatory signaling pathways is a promising approach for treating inflammatory diseases. Herein, a multifunctional nanosystem is developed for active targeting, activatable imaging and on‐demand therapy against inflammatory diseases through modulating inflammatory pathways. A chromophore‐drug dyad (QBS‐FIS) is synthesized by linking a chromophore and a Nrf2 (nuclear factor E2‐related factor) activator fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Alcohol-induced cascade signaling reactions are usually thought to be initiated via Nrf2/HO-1 pathway. , It has been suggested that HO-1 may be a potential target for the interaction of inflammation and oxidative stress in ALD . When the degree of alcohol-induced liver injury worsens, the expression level of the HO-1 protein tends to decrease, which is probably due to the inhibitory effect.…”
Section: Resultsmentioning
confidence: 99%
“…Alcohol-induced cascade signaling reactions are usually thought to be initiated via Nrf2/HO-1 pathway. , It has been suggested that HO-1 may be a potential target for the interaction of inflammation and oxidative stress in ALD . When the degree of alcohol-induced liver injury worsens, the expression level of the HO-1 protein tends to decrease, which is probably due to the inhibitory effect.…”
Section: Resultsmentioning
confidence: 99%
“…Wu, Tian, and Zeng et al reported a ROS-activatable multifunctional nanosystem for liver and kidney inflammation diagnosis and therapy through modulating inflammatory pathways [ 121 ]. As presented in Figure 6 , an AIEgen was linked with a Nrf2 activator fisetin through boronate bond, in which the fluorescence would be quenched and the boronate bond could be cleaved by ROS.…”
Section: Detection Of Reactive Oxygen Nitrogen Speciesmentioning
confidence: 99%
“…Fluorescence imaging in the near-infrared second window (NIR-II, 900–1700 nm emission) has innate advantages of weak scattering of light and little autofluorescence in tissues, thus allowing imaging of organisms in a real-time way with higher resolution and at greater depth, facilitating more accurate disease diagnosis, and understanding of disease progression. An optoacoustic (photoacoustic) imaging method images a sample with large penetration depth and high resolution by collecting ultrasound waves produced by photoabsorbers in the sample. Especially, multispectral optoacoustic tomography (MSOT) is more advantageous, since this imaging technique detects the ultrasound signals produced by various photoabsorbers in the sample by irradiating the sample with laser light of multiple wavelengths; and the determination of the spectral identity of each photoabsorber is achieved by spectral unmixing so that the optoacoustic signal of a specific photoabsorber can be tracked. In addition, 3D (three-dimensional) images can be easily acquired or generated, thus facilitating accurate localization of the disease site and assessment of its size. A probe suitable for NIR-II fluorescent and optoacoustic dual-mode imaging is very advantageous as it can provide mutually corroborating information. ROS with hydrogen peroxide being the most abundant member has an important part to play in the onset and development of AKI such as contrast-agent-induced renal injury and ischemia/reperfusion-induced renal injury. , At the site of kidney injuries, elevated levels of ROS including H 2 O 2 lead to enhanced oxidative stress and correspondingly result in increased tissue damage and exacerbated inflammation. , Therefore, endogenous hydrogen peroxide at the site of renal injury could be a promising in situ biomarker, , and thus noninvasive in situ detection of the biomarker through NIR-II fluorescence imaging and optoacoustic imaging using an effective probe would be ideal for accurate localization of the site of AKI.…”
Section: Introductionmentioning
confidence: 99%